Molecular Analysis of a Short-term Model of β-Glucans-Trained Immunity Highlights the Accessory Contribution of GM-CSF in Priming Mouse Macrophages Response - Sarah Walachowski; Guillaume Tabouret; Marion Fabre; Gilles Foucras (Frontiers in Immunology, 2017)
β-Glucans (BGs) are glucose polymers present in the fungal cell wall (CW) and, as such, are recognized by innate immune cells as microbial-associated pattern through Dectin-1 receptor. Recent studies have highlighted the ability of the pathogenic yeast Candida albicans or its CW-derived β(1,3) (1,6)-glucans to increase human monocytes cytokine secretion upon secondary stimulation, a phenomenon now referred as immune training. This ability of monocytes programming confers BGs an undeniable immunotherapeutic potential. Our objective was to determine whether BGs from Saccharomyces cerevisiae, a non-pathogenic yeast, are endowed with such a property. For this purpose, we have developed a short-term training model based on lipopolysaccharide re-stimulation of mouse bone marrow-derived macrophages primed with S. cerevisiae BGs. Through a transcriptome analysis, we demonstrated that BGs induced a specific gene expression signature involving the PI3K/AKT signaling pathway as in human monocytes. Moreover, we showed that over-expression of Csf2 (that encodes for GM-CSF) was a Dectin-1-dependent feature of BG-induced priming of macrophages. Further experiments confirmed that GM-CSF up-regulated Dectin-1 cell surface expression and amplified macrophages response along BG-mediated training. However, the blockade of GM-CSFR demonstrated that GM-CSF was not primarily required for BG-induced training of macrophages although it can substantially improve it. In addition, we found that mouse macrophages trained with BGs upregulated their expression of the four and a half LIM-only protein 2 (Fhl2) in a Dectin-1-dependent manner. Consistently, we observed that intracellular levels of FHL2 increased after stimulation of macrophages with BGs. In conclusion, our experiments provide new insights on GM-CSF contribution to the training of cells from the monocytic lineage and highlights FHL2 as a possible regulator of BG-associated signaling.